LIFE CYCLE OF HOLOTRICHIA KARSCHI BRENSKE (COLEOPTERA: SCARABAEIDAE: MELOLONTHINAE) - G. P. BHAWANE; S. M. GAIKWAD; A. B. MAMLAYYA; S. R. ALAND (The Bioscan, 2011)
The soil dwelling insect pests causing damage to crops are mainly the white grubs, termites, cutworms, wireworms etc. Among these white grub has recognized as the pest of national importance. Adults of Holotrichia karcshi Br. were collected form Amba Reserve Forest of Kolhapur district which comes under the Western Ghats. Mated Female laid the eggs singly at a depth of 5- 10 cm in the soil. The incubation period of the eggs was ranged from 10 to 16 days. The first instar lasted 12 to 16 days. The subsequent second and third instars were lasted for 29 to 32 and 25 to 30 days respectively. The pupal period was recorded about 17 to 20 days. Adult longevity was observed in laboratory conditions. It took 14 to 25 days. Studies on the host range revealed that adult feed on the foliage of seven different plants according to their distribution and availability.